Cooling tower: an energy conservation resource - Mohiuddin, A. K. M.; Kant, Keshav (Institution of Engineers, Bangladesh, 1992)
In order ot achieve a higher level of performance of a cooling tower, various sub-systems of the tower should be refined and fine tuned to work together as a coherent system. Keeping in veiw the performance of a cooling tower analyses of the various sub-systems namely (a) air inlet system, (b) fill or packing (c) water distribution system (d) drift eliminators and (e) fan and associated equipment are presented here. Energy consumption by the tower sub-systems to the optimal extent only plays a key role in the energy conservation. Experiments with a cellular type of packing gave a fairly small pressure drop. Experiments also carried out with various types of drift eliminators namely cellular type and those made of Wood, Cement Asbestos and Concrete showed minimum pressure drops for the cellular type of drift eliminators. The selection, thus of a right kind packing and drift elimonator with smaller pressure drops (resistance) can result in a substantial energy conservation in the tower.